THE EFFECTS OF CULTURE ON MANAGEMENT ACCOUNTING-A SYSTEMATIC REVIEW - Ula Restu Rafifah; Lu’lu’ Nafiati; Dewi Fitriyani; Aditya Candra Kusuma; Miswanto Miswanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Culture has received a large amount of interest in the management accounting literature. We present the first structure of the article studying culture in management accounting. Our search yielded 51 papers published in eight leading journals between 2001 and 2020. This study provides a critical review of the findings of cultural research in the last 20 years in the management accounting literature and summarizes the contributions of previous research to the management accounting literature. We find that culture emerges as a relevant variable in the field of management accounting, particularly management control systems. The results of this study indicate that there is a shift in the trend of cultural research in the management accounting literature which initially focused on Hofstede's national culture. This shift was triggered by one of the criticisms by Baskerville (2003) who criticized Hofstede's concept of national culture. The study also identifies gaps in published research for future research. Keywords: Culture; cultural; country; nation; literature review